First year nursing students' perceptions of learning interpersonal communication skills in their paid work: A multi-site Australasian study. (October 2020) - Crawford, Ruth; McGrath, Belinda; Christiansen, Angela; Roach, David; Salamonson, Yenna; Wall, Peter; Ramjan, Lucie M.
Abstract: Nursing students are increasingly undertaking paid work while studying and most choose paid work in health care or hospitality. This paper is drawn from a larger sequential exploratory mixed-method study which examined the relationship between students working while studying nursing and the impact on academic performance. In this paper, we explored first year nursing students' perceptions of communication skills gained through paid work. Using a qualitative exploratory design, 50 first year commencing nursing students from four nursing schools (3 Australia; 1 New Zealand) were interviewed. Inductive thematic analysis was used which identified two themes: (i) recognising the value of learning interpersonal communication skills and; (ii)opportunities to develop effective interpersonal communication skills. Paid work provides interpersonal communication skills; active listening, being present and interacting while multi-tasking and emotion management. Undergraduate education providers need to recognise the benefits of paid work for students, including enhancing interpersonal skills. Highlights: Engaging in paid employment while studying has benefits for nursing students. First year nursing students recognise their paid employment gives them valuable communication skills. Paid employment increases confidence, promotes active listening and empathy. Students in paid employment while studying acquire skills in self and others' emotion management. Education providers need to recognise the benefits of paid employment.